PENGARUH KOMPOSISI MEDIA TANAM DAN DOSIS BIOPESTISIDA NABATI TERHADAP PRODUKSI TOMAT - wahyu fikrinda; Edyson Indawan; Regina Magi Ni Ga; I Made Indra Agastya (Jurnal Penelitian Pertanian Terapan, 2020)
Tomatoes are important vegetable commodities and have high nutritional value. Until now, tomato productivity was still quite low at 16.09 - 18.63 tonnes/ha from 2015 to 2019 when compared to its potential which could reach 20-30 tonnes/ha. One of the ways to increase the productivity of tomato plants is to improve cultivation techniques, especially the use of suitable planting media and pest control by utilizing natural materials. The composition of the media that was suitable for tomato plants needs to be known to produce high-quality and high-yielding tomatoes. Bio-pesticide application using several plants with the appropriate dosage can be an alternative to reduce the use of chemicals. This study aimed to determine the composition of the plant media and the effectiveness of biopesticides to increase the production of tomato plants. The study used Completely Randomized Design (CRD) two factors, where the first factor is the composition of the growing media and the second factor is the dosage of vegetable biopesticides. The first factor is the composition of the growing media consisting of 4 levels, namely K0 (without bokashi), K1 (Soil: Bokashi = 11: 1 (W/W) per polybag, K2 (Soil: Bokashi = 5: 1 (W/W) per polybag), K3 (Soil: Bokashi = 3: 1 (W/W) per polybag. The second factor is the dosage of vegetable biopesticides consisting of 4 levels, namely A0 (control), A1 (20 ml per polybag), A2 (40 ml per polybag), A3 (60 ml per polybag). Each treatment consisted of 4 levels of treatment and was repeated 4 times so that there are 64 experimental units. The data were analyzed using analysis of variance, and the real effect then tested further using Least Significance Different at 5% level. The results showed that there was an interaction between the treatment of the composition of the planting medium and the biopesticide on the parameters of plant height, number of leaves, leaf area, number of fruits, fruit weight, and production. The composition of the soil growing media composition: bokashi (5:1) and 40 ml biopesticide (K2B2) produced the highest number of fruit which was 255.53 fruit, the largest fruit weight was 7.67 kg per plant and produce 10.22 tonnes/ha. The use of biopesticides is effectively applied to tomato plants so that it can reduce the number of plants affected by fusarium wilt disease. the ones with the highest number of healthy plants were in A2 treatment with a pesticide dose of 40 ml per plant at 81.25%.